Association of Sympathetic Activity with Body Mass Index in Male Adults of North Indian by Hand Grip Dynamometer - Kumar, Rovins; Verma, Anjali; Kumar, Jay Ballabh; Adhana, Ritu (Asian Journal of Medical Research, 2021)
Background: The most significant determinants of hypertension have been established as obesity and overweight. The positive relationship between handgrip intensity and Blood Pressure could be clarified by several mechanisms. Subjects and Methods: Body mass index, Hand grip dynamometer and Blood pressure of the n= 120 subjects, age =18-25. The blood pressure and hand grip dynamometer test was recorded by following standard procedure. Results: The finding of this study is sympathetic activity was increased in overweight and in obese as compared to normal body mass index hand grip dynamometer test. Conclusion: The sympathetic activity was increased in overweight and in obese subjects as compared to normal body mass index after hand grip dynamometer test.